Antioxidant Protection against Trastuzumab Cardiotoxicity in Breast Cancer Therapy - Gabriel Méndez-Valdés; Francisca Gómez-Hevia; Maria Chiara Bragato; José Lillo-Moya; Catalina Rojas-Solé; Luciano Saso; Ramón Rodrigo (Antioxidants, 2023)
Breast cancer is the most frequent malignant neoplastic disease in women, with an estimated 2.3 million cases in 2020 worldwide. Its treatment depends on characteristics of the patient and the tumor. In the latter, characteristics include cell type and morphology, anatomical location, and immunophenotype. Concerning this latter aspect, the overexpression of the HER2 receptor, expressed in 15–25% of tumors, is associated with greater aggressiveness and worse prognosis. In recent times some monoclonal antibodies have been developed in order to target HER2 receptor overexpression. Trastuzumab is part of the monoclonal antibodies used as targeted therapy against HER2 receptor, whose major problem is its cardiac safety profile, where it has been associated with cardiotoxicity. The appearance of cardiotoxicity is an indication to stop therapy. Although the pathophysiological mechanism is poorly known, evidence indicates that oxidative stress plays a fundamental role causing DNA damage, increased cytosolic and mitochondrial ROS production, changes in mitochondrial membrane potential, intracellular calcium dysregulation, and the consequent cell death through different pathways. The aim of this review was to explore the use of antioxidants as adjuvant therapy to trastuzumab to prevent its cardiac toxicity, thus leading to ameliorate its safety profile in its administration.